Spontaneous Coronary Artery Dissection and Implantation of Absorb Bioresorbable Drug-Eluting Stent in Cocaine-Related Acute Coronary Syndrome - Ceravolo, Roberto; Vatrano, Marco; Dattilo, Giuseppe; Ferraro, Alessandro; Antonio Ciconte, Vincenzo; Imbalzano, Egidio (Journal of Cardiovascular Medicine and Cardiology, 2014)
The spontaneous dissection of the coronary arteries (SCAD) is rare and few data are available in the worldwide literature. Several diseases and conditions have been associated with SCAD, such as atherosclerosis, connective tissue disorders and the peripartum episode. Cocaine addiction is one of causes of the disease in young patients. In this paper we present a case report of a patient with a acute coronary syndrome who had a history of recent cocaine abuse. The coronary angiography showed spasm and spontaneous dissection of the left anterior descending artery with a slow coronary flow. Based on the clinical and angiographic characteristics of the patient, we decided to perform a coronary angioplasty with bioresorbable vascular scaffold stent placement.